Carbon emission reduction pathways under carbon neutrality targets in Gansu province of China - Xie, Mingjun; Liu, Xinyuan; Yan, Wenshan; Li, Yongjun; Liu, Xinwei; Zhang, Gexiang; Sun, Jianyun (Frontiers in Environmental Science, 2022)
Gansu province will fulfill the carbon reduction target under the national carbon neutrality strategy. As a less developed region in China, Gansu will have to trade off carbon reduction targets and economic development. This study adopts a computable general equilibrium model to simulate the carbon reduction pathway and estimate the possible impacts on the economy, output and environment under a carbon-neutral target. Our results show carbon emission will peak around 2033 in baseline scenario and decline slowly after the peak. While carbon emissions will peak around 2023 in carbon neutral scenario and decline very fast from 154 million ton in 2023 to 40 million ton in 2060. The economy will continue to increase from106 billion USD in 2017 to 477 billion USD in 2050 underwith carbon reduction target, which means carbon neutral target will have very limited impacts on the economy by 2060. At the sector level, economic outputs various among different sectors. Output will increase significantly, e.g. power generation 14%, water supply 8% and nonmental 4%. While some other sector will decrease quickly, paper 15% and textile industry 7%. Carbon reduction will also contribute to air pollutants reduction, which is the benefit to air quality. Carbon neutral target will bring more opportunities in Gansu due to green energy potential without economic burden. Proper carbon mitigation policy would avoid the adverse impact but bring more potential to the economy in Gansu.